Perancangan Buku Ilustrasi Tentang H.O.S. Tjokroaminoto Sebagai Teladan bagi Anak Indonesia - Yanuar Aldin; Aditya Rahman Yani; Masnuna (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2022)
Children as Indonesia's next generation should know and imitate the stories of great people who were born in their nation so that they can inspire and build their dreams from an early age. One of the great figures who deserve to be emulated by the younger generation of the Indonesian nation is HOS Tjokroaminoto who has played a major role in the struggle for Indonesian independence. However, instilling an example to children is not an easy thing, therefore it requires media that is attractive and easily understood by them. One of the media that has this critique is illustration books, which are designed with a visually appealing concept, and the contents of books can inspire children. This research is about how to design an illustrative book about HOS Tjokroaminoto that is interesting and inspiring for children aged 9-11 years. This study uses data collection methods in the form of interviews, observations, and questionnaires. Then the collected data were analyzed using the descriptive analysis method to find new ideas about illustration book design.